Ichthyotoxicity of four species of gymnodinioid dinoflagellates (Kareniaceae, Dinophyta) and purified karlotoxins to larval sheepshead minnow - Mooney, B; Gustaaf Hallegraeff; Place, AR (2010)
Two species of Kareniaceae, Karlodinium veneficum (Swan and Huon River isolates) and Karlodinium conicum, and their respective purified karlotoxins (KmTx), were investigated for ichthyotoxicity on larval sheepshead minnow. Two non-karlotoxin producing species, Karenia mikimotoi and Karlodinium ballantinum were also tested. Algal treatments included live and lysed cells (homogenized and CuSO4 treated) with fishmortalities observed from lysed Ka. veneficum and Ka. conicum but none observed from K. mikimotoi and Ka. ballantinum. The variance in ichthyotoxicity between live and lysed cells of Ka. veneficum(Swan and Huon River) and Ka. conicum(Southern Ocean) confirm that toxin is cell bound and ichthyotoxicity increases upon lysis. Ichthyotoxic blooms of Ka. veneficum in situ in the Swan River, Western Australia and Chesapeake Bay, Maryland, USA are unrelated to algal cell density as mortality was observed with low densities. In laboratory treatments, no fish mortalities were observed upon exposure to live intact cells of all four species at algal concentrations up to 2.5-105 cells/mL in replete nutrient growth conditions. Lysed low density (3-104 cells/mL) Ka. veneficum (Swan and Huon River) grown under P-limited nutrients caused quicker fish mortality than those cultured in replete nutrient conditions. Pure toxin isolated from Ka. veneficum (Swan and Huon River) and Ka. conicum (Southern Ocean) were toxic to sheepshead minnow larvae, with the lethal dose lowest for KmHuonTx 2 (508.2 ng/ mL), followed by KmSwanTx 2-1 (563.2 ng/mL), and KmconicumTx (762.4 ng/mL).